Pelatihan Pemanfaatan Aplikasi Zahir Accounting di SMA Muhammadiyah 4 Jakarta - Andi Amri; Ade Putri Muliya; Aryo Alamsyah; Whiz Alriz Luth’v Alriz Luth’v (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Accounting computerisation is the process of processing accounting data from manual to automatic using computer media which aims as a tool to facilitate effective and efficient recording work. The use of accounting computers has been widely used in various companies and even introduced in vocational schools, one of which is MYOB Accounting. However, among high school students this is something new. This is evidenced by the low understanding of students, especially SMA Muhammadiyah 4 Jakarta, in using accounting computer applications. In addition, the software chosen is Zahir Accounting which is not popular among academics but this application is an Indonesian product that should be introduced in education in schools and lectures. The purpose of this service is to provide training to Economics teachers and students of SMA Muhammadiyah 4 Jakarta regarding the use of the Zahir Accounting application. At least the theoretical in using this application can be well understood to all audiences. Respondents involved were definitely Economics teachers and social studies students with a total of 45 people. The results of the service show that the service activities are carried out in 5 steps, namely the start-up, socialisation, preparation, implementation, and evaluation stages. Based on these five stages, it can be obtained that there is an increase in knowledge and practicum in using the Zahir Accounting application so that in the future there will be an increase in productivity and management of teachers and students at SMA Muhammadiyah 4 Jakarta. Meanwhile, the results of this service can be a recommendation for the leadership of SMA Muhammadiyah 4 Jakarta in improving the skills and abilities of teachers and students in using Zahir Accounting which will later be included as one of the materials in the syllabus.